PERTUMBUHAN DAN HASIL TOMAT PADA DUA SISTEM BEDENGAN DAN PEMBERIAN PEMBENAH TANAH DENGAN DOSIS YANG BERBEDA DI TANAH VERTISOL LOMBOK - Cahyani, Karnila; Suheri, Herman; Farida, Nihla (Fakultas Pertanian Universitas Mataram, 2024)
This article is the result of an experiment that aims to determine the effect of rorak and conventional bed systems given soil ameliorant in various doses on the growth and yield of tomato. The experiment was carried out in Lombok vertisol soil using Group Randomized Design. The soil ameliorant was applied as a mixture of manure and rice husk charcoal (1: 1) with the following doses: no ameliorant, 5 tons/ha, 10 tons/ha), and 15 tons/ha. The experimental results analyzed based on factorial anova indicated that bedding type had a significant effect on the number of branches per plant, total fruit weight per plant, fruit weight per plot and potential fruit weight per hectare. Conventional beds are higher in plant growth, while rorak beds are higher in plant yield. Application of soil ameliorant had no significant effect on all observed parameters. The interaction of bedding type and dosage of soil ameliorant had no significant effect on all observed parameters.